Enzymes of the AKR1B and AKR1C Subfamilies and Uterine Diseases - Lanisnik Rizner, Tea (Frontiers in Pharmacology, 2012)
Endometrial and cervical cancers, uterine myoma, and endometriosis are very common uterine diseases. Worldwide, more than 800,000 women are affected annually by gynecological cancers, as a result of which, more than 360,000 die. During their reproductive age, about 70% of women develop uterine myomas and 10–15% suffer from endometriosis. Uterine diseases are associated with aberrant inflammatory responses and concomitant increased production of prostaglandins (PG). They are also related to decreased differentiation, due to low levels of protective progesterone and retinoic acid, and to enhanced proliferation, due to high local concentrations of estrogens. The pathogenesis of these diseases can thus be attributed to disturbed PG, estrogen, and retinoid metabolism and actions. Five human members of the aldo-keto reductase 1B (AKR1B) and 1C (AKR1C) superfamilies, i.e., AKR1B1, AKR1B10, AKR1C1, AKR1C2, and AKR1C3, have roles in these processes and can thus be implicated in uterine diseases. AKR1B1 and AKR1C3 catalyze the formation of PGF2α, which stimulates cell proliferation. AKR1C3 converts PGD2 to 9α,11β-PGF2, and thus counteracts the formation of 15-deoxy-PGJ2, which can activate pro-apoptotic peroxisome-proliferator-activated receptor γ. AKR1B10 catalyzes the reduction of retinal to retinol, and thus lessens the formation of retinoic acid, with potential pro-differentiating actions. The AKR1C1–AKR1C3 enzymes also act as 17-keto- and 20-ketosteroid reductases to varying extents, and are implicated in increased estradiol and decreased progesterone levels. This review comprises an introduction to uterine diseases and AKR1B and AKR1C enzymes, followed by an overview of the current literature on the AKR1B and AKR1C expression in the uterus and in uterine diseases. The potential implications of the AKR1B and AKR1C enzymes in the pathophysiologies are then discussed, followed by conclusions and future perspectives.